Policy-based management of content distribution networks. - Verma, D.C.
We present a policy-based architecture for the control and management of content distribution networks that form an overlay of caching proxies over an underlying physical network. The architecture extends the policy framework used for controlling network quality of service (QoS) and security to content distribution networks. The fundamental advantage of a policy-based framework is that it allows a machine-independent scheme for managing multiple devices from a single point of control. In this article we describe this architecture and demonstrate how it enables dynamic updates to content distribution policies. Furthermore, we analyze the impact of such dynamic distribution on the cost of content serving
Keywords: QoS; Caching proxies; Content distribution networks; Content serving; Control; Dynamic distribution; Dynamic updates; Machine-independent scheme; Policy framework; Policy-based architecture; Policy-based management; Quality of service; Security; Underlying physical network